Pendidikan Islam Perspektif Syed Naquib Al Attas: Makna Pendidikan Islam Ta’dib serta Klasifikasi Ilmu - Edy, Edy; Permata Sari, Intan (STIT Sirojul Falah Bogor, 2022)
Education is the joint of life, so that humans are able to solve the problems that occur on this earth. According to Al Attas adab is one of the typical terms in the tradition of the development of Islamic education. Adab is the main key in Islamic education. Therefore, Al Attas needs to give a new meaning to the term adab. Al Attas agrees with linguists regarding the meaning of the word adab, Al Attas states that adab is the right action, springs from self-discipline built on knowledge, and comes from wisdom. This research is descriptive qualitative with a library research approach, which focuses more on collecting data from various relevant data sources. This includes books, internet, and research results related to the title of this scientific work. The results showed that according to Syed Muhammad Naquib Al-Attas' view, Islamic education is a process of inculcating knowledge into human beings. In the current Millennial era, the name Al Attas deserves to be equated with the names of world scientists such as Ismail Razi Al Faruqi, Fazlur Rahman as a contemporary Muslim scientist. Al Attas is one of the most influential scientists in this millennial era, Al Attas is not changing the laws or principles of education in Islam, but making new changes in developing the Islamic education system. Keywords: Adab, Islamic education , Syed Naquib Al Attas